2005
DOI: 10.1073/pnas.0508001102
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis required for long-term memory is induced by PKC activation on days before associative learning

Abstract: Protein synthesis has long been known to be required for associative learning to consolidate into long-term memory. Here we demonstrate that PKC isozyme activation on days before training can induce the synthesis of proteins necessary and sufficient for subsequent long-term memory consolidation. Bryostatin (Bryo), a macrolide lactone with efficacy in subnanomolar concentrations and a potential therapeutic for Alzheimer's disease, is a potent activator of PKC, some of whose isozymes undergo prolonged activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 41 publications
4
56
0
1
Order By: Relevance
“…The anisomycin-bryostatin study confirmed the results of other studies Alkon et al, 2005) showing that protein synthesis is involved in memory storage and its subsequent recall. Animals that had received 2-paired TEs plus bryostatin (0.25 ng/ml) and then were tested for recall at 4 h showed positive CRs with the CS alone.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The anisomycin-bryostatin study confirmed the results of other studies Alkon et al, 2005) showing that protein synthesis is involved in memory storage and its subsequent recall. Animals that had received 2-paired TEs plus bryostatin (0.25 ng/ml) and then were tested for recall at 4 h showed positive CRs with the CS alone.…”
Section: Resultssupporting
confidence: 80%
“…The dose response results with Hermissenda were congruous with the published data for several model systems (Favit et al, 1998;Wender et al, 1998;Etcheberrigaray et al, 2004;Scioletti et al, 2004;Alkon et al, 2005). Subnanogram concentrations of bryostatin administered before paired associative conditioning up-regulated PKC activity, and specifically for Hermissenda, enhanced both acquisition and retention initiated by suboptimal paired CS/US training regimes.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Bryostatin-1, which crosses the blood-brain barrier when administered peripherally (28), produces a relatively selective activation of the PKC isozyme, which is neuroprotective (29)(30)(31) and has a lower median effective dose than PKC␦ for bryostatin-1 in its translocation (thus activation), whereas PKC␦ is most likely involved in ischemic injury during ischemia-reperfusion (32)(33)(34). We recently showed that PKC activation with bryostatin-1 enhanced exactly those synaptogenesis, presynaptic/postsynaptic ultrastructural specialization, and protein synthesis functions involved in rat maze learning and memory (20,35). PKC activation has at least two actions that may be relevant to PKC signal processing: activation of PKC isozymes at low concentrations and protection of active, membrane-bound PKC from degradation under stress.…”
Section: Resultsmentioning
confidence: 99%